Gravettian hunting and exploitation of bears in Central Europe. (2nd March 2015) - Wojtal, Piotr; Wilczyński, Jarosław; Nadachowski, Adam; Münzel, Susanne C.
Abstract: Evidence of hunting and exploitation of cave bears ( Ursus spelaeus, sensu lato) are recently documented in western and eastern sites of its former European distribution in Middle and Upper Palaeolithic contexts. Human hunting and exploitation has always been accepted for brown bears ( Ursus arctos ) but not for cave bears. Recently in Hohle Fels (Swabian Jura), a vertebrae was found with an embedded flint projectile. Furthermore, cut and impact marks document processing of this game. Alongside cave bear, small numbers of coeval brown bears are always present in caves. In open-air sites, both bear species are recorded in low but equal numbers. The question why U. arctos survived the Last Glacial Maximum (LGM) still remains open. In this respect, the Gravettian is the crucial period for these questions, as the latest dates for cave bears fall into this time span. The question of whether hunting by Neanderthals or Anatomically Modern Humans (AMH) had an impact on the demise and final extinction of cave bears is discussed, considering ecological and behavioural parameters. In this context, Hohle Fels Cave from the Swabian Jura (Germany), and Deszczowa Cave in the Krakowsko-Częstochowska Upland (Poland), as well as five open air sites in the Czech Republic and one from Poland are discussed.